MIEJSKIE STRATEGIE I TAKTYKI WOKÓŁ KONCEPCJI PRAKTYKI ŻYCIA CODZIENNEGO MICHELA DE CERTEAU - Miciukiewicz, Konrad (Wydział Prawa i Administracji UAM, 2008)
This paper comments on the problems of urban space production with regard to Michel de Certeau’s theory of the practice of everyday life. It attempts to link the analysis of strategic actions of architects and town planners with the research on the spatial practices of the everyday and the individual cognitive mappings of urban space. The author points out the problematic character of the application of the dualistic social practice concept. On the one hand, as a result of various turns in urban planning (communicative, cultural, interpretative, etc.) the architects are more sensitive to the problems o f everyday life. On the other, due to the increasing fear of crime and terrorism, the practices of the urban dwellers have become more instrumental and rationalised.
URBAN STRATEGIES AND TACTICS: ON THE MICHEL DE CERTEAU’S THEORY OF EVERYDAY LIFE